2013
DOI: 10.1097/hco.0b013e32835c5492
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure with preserved ejection fraction

Abstract: Although enormous strides have been made in understanding the pathophysiology and refining the diagnostic criteria of HFpEF, there is currently no pharmacological therapy with mortality benefits. Further characterization and the recruitment of more homogeneous patient populations will be essential to identify effective treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 81 publications
2
31
0
Order By: Relevance
“…Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT), a large trial of spironolactone (N=3445) in more symptomatic, advanced HFpEF is still in progress [3]. Better understanding of pathophysiology of HFpEF has identified new drug targets [64]. A small trial with a short follow-up period showed significant improvement in pulmonary pressure, right ventricular function, and LV relaxation and distensibility with the use of sildenafil in HFpEF patients who had evidence of superimposed PAH [65].…”
Section: Lesson #8: It Is Possible To Treat Hfpef—treat Now By Treatimentioning
confidence: 99%
“…Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT), a large trial of spironolactone (N=3445) in more symptomatic, advanced HFpEF is still in progress [3]. Better understanding of pathophysiology of HFpEF has identified new drug targets [64]. A small trial with a short follow-up period showed significant improvement in pulmonary pressure, right ventricular function, and LV relaxation and distensibility with the use of sildenafil in HFpEF patients who had evidence of superimposed PAH [65].…”
Section: Lesson #8: It Is Possible To Treat Hfpef—treat Now By Treatimentioning
confidence: 99%
“…13 HF has historically been attributed to systolic dysfunction, as evidenced by a LV ejection fraction of ≤ 45%. This HF phenotype is now referred to as HF with reduced ejection fraction (HFrEF) and is characterized by a progressive ventricular dilation.…”
Section: Introductionmentioning
confidence: 99%
“…1 In contrast to HFrEF, individuals with HFpEF generally are older, more likely to be female, and have a lower incidence of coronary artery disease but greater occurrence of atrial fibrillation. 3 A leading cause of HFpEF is hypertension, and the sine qua non of HFpEF is diastolic dysfunction or impaired relaxation of the LV. Although both forms of HF occur at similar prevalences, HFpEF is increasing at a steady rate and is anticipated to become the most common type of HF in the next 10 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition of HF with preserved ejection fraction (HFpEF) is thought to be more common in women and more prevalent in the elderly, with similar mortality rates as HFrEF (1215). HFpEF is documented as the leading cause of hospital admission in patients over 65 years of age and is predicted to be the leading cause of HF within a decade (16, 17). Notably, HFpEF is a leading cause of pulmonary hypertension (HTN) (18).…”
Section: Introductionmentioning
confidence: 99%